2021
DOI: 10.4491/eer.2020.672
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanomaterial from industrial waste and its application in environmental pollutant remediation

Abstract: Increased productions of waste from industries have persuaded in sustainable and naturally stable methods to reuse the waste. Utilization of wastes for the synthesis of nanomaterial is of significant importance due to its extensive variety of uses in various industrial sectors. This review focuses on potential options available for nanomaterial synthesis from waste produced by industrial activities and manufacturing processes. Possible application of industrial waste derived nanomaterial for the expulsion of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 125 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…It was also observed that the CNi0.05 sample had a more uniform grain shape compared to the CNi0.1 sample. The small and homogeneous particle shape was very beneficial for its application as a photocatalyst because it provides a larger contact area between the catalyst and the substrate [39].…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that the CNi0.05 sample had a more uniform grain shape compared to the CNi0.1 sample. The small and homogeneous particle shape was very beneficial for its application as a photocatalyst because it provides a larger contact area between the catalyst and the substrate [39].…”
Section: Characterizationmentioning
confidence: 99%
“…The higher degradation of Methylene Blue even at higher concentration was due to its simpler structure, bearing an azo group which is easier to break in photocatalysis (Inset of Fig. 6b) [39]. The simultaneous degradation process was evaluated by mixing the optimal concentration of Rhodamine B (10 mg L -1 ) and Methylene Blue (20 mg L -1 ) solutions at various volume ratios (Table S1).…”
Section: Photocatalytic Properties Assaymentioning
confidence: 99%
“…The relentless pursuit of material performance extremes has always been one of the critical driving forces in human societal development. 1 Throughout several industrial revolutions, explosive technological advancements have significantly altered our lives while also precipitating a series of formidable global challenges, such as energy crises, environmental pollution, and various derivative issues. [2][3][4][5] In response to these challenges, various emerging advanced technologies have been developed in recent years, encompassing energy storage and conversion, gas separation, air filtration, and water purification, striving to meet intensive energy-related demands and address multifaceted environmental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, these adsorbents usually suffer from low adsorption capacities or removal efficiencies of heavy metal ions. Recently, considerable studies concerning the use of nano adsorbents for the removal of heavy metals from industrial effluent have been done [19]. Metals oxides like magnesium oxide nanoparticles (nMgO) have attracted researchers worldwide due to its large specific surface area, low-density, non-toxicity, cheap manufacturing, and better physical characteristics which can efficiently remove heavy metals [20].…”
Section: Introductionmentioning
confidence: 99%